Letter - Araquistain, Luis, 1886-1959
1940-11-13 013-0068-001 4, Warnborough Road Oxford. 13th November 1940 Sir Walter Citrine Dear Sir Walter, In to-day's Evening Standard, Late Special edition, page 7, column 4, I read that Largo Caballero is going to be tried by a court-martial in Madrid. The news comes like a thunderbo[l]t to me. If it is true, it means that he has been handed over to Franco by the traitors of Vichy. He was in the unoccupied zone in the South of France. You know what Largo Cabellero has been in the Spanish Labour movement and I hope that the British Trade Unions will not remain indifferent to his tragical fate. If nothing is done for him, it is certain that he will be shot. I am aware, of course, of the delicate situation 292/946/13/68(i)